Infini-Rien: Ist Pascals Wettargument formallogisch ungültig? - Hoffmann, Christian (Archiv für Geschichte der Philosophie, 2022)
In the Infini-Rien fragment of his Pensées, Blaise Pascal develops an argument for the rationality of faith in God, which posthumously became known as Pascal's Wager and at the same time represents a cornerstone of modern probability theory. While this betting argument has been the subject of much philosophical investigation, the contribution of this paper lies in the following: On the one hand, the bet is reconstructed in its basic features as well as its structure with the help of modern decision and probability theory tools. Thus, it is shown that Pascal's betting argument, in distinction to Hacking 1972 for instance, has the form of an a fortiori argument. On the other hand, as far as objections to Pascal's argument are concerned, it is true that the premises have often been called into doubt, more or less convincingly. On the other hand, this article is dedicated to the question, often emphatically – especially in Hacking 1972 – and perhaps carelessly affirmed in Pascal research, whether Pascal's premises imply his conclusion at all.